Symptom burden profiles and influencing factors in convalescent stroke patients: a latent profile analysis - Xiaojiao Huang; Ying Peng; Kebing Zhou; Yelin Ji; Qingqing Wang; Yanfang Deng; Zhilian Huang; Fengxia Yan (BMC Neurology)
Abstract Background With advancements in acute stroke treatments, more patients receive timely interventions and survive. However, during the recovery phase, stroke patients often experience a range of coexisting symptoms, which contribute to significant physical and psychological distress and hinder rehabilitation outcomes, thereby exacerbating their symptom burden. Addressing the symptom burden and implementing precise management strategies are therefore essential to improve the quality of life and rehabilitation outcomes of convalescent stroke patients. This study aimed to identify the symptom burden profiles of convalescent stroke patients and explore the factors influencing these profiles. Methods This was a cross-sectional study. A total of 330 convalescent stroke patients who were hospitalized in a tertiary hospital in Guangdong Province were selected as survey subjects. A demographic and clinical characteristics questionnaire, the Symptom Experience Scale for Stroke Survivors, the Fear of Progression Questionnaire-Short Form, and the Acceptance of Illness Scale were used for the investigation. Latent profile analysis of symptom burden in convalescent stroke patients was conducted, and the factors influencing the latent profiles were explored by unordered logistic regression analysis. Results The symptoms of convalescent stroke patients are complex, with the top five common symptoms being: fatigue (88.2%), moodiness (79.4%), unilateral limb weakness (79.1%), slower response (70.0%), and uncoordinated movement (68.8%). Symptom burden of convalescent stroke patients was divided into three categories: low symptom burden group (40.7%), moderate symptom burden group (36.8%), and high symptom burden - somatic discomfort group (22.5%). The unordered logistic regression analysis indicated that age, daily caregiver status, self-care ability, fear of disease progression, and illness acceptance were influential factors across different potential categories. Conclusion There was heterogeneity in symptom burden among convalescent stroke patients. Clinicians should tailor interventions to the distinct symptom profiles and influencing factors of stroke patients in the recovery period. Targeted interventions should focus on elderly patients and those who experience fear of disease progression, as this may be an effective approach to alleviate symptoms in the moderate symptom burden group and the high symptom burden - somatic discomfort group.